The European Union Digital Single Market Europe's Digital Transformation - Dąbrowski, Łukasz Dawid; Suska, Magdalena (Routledge Studies in the European Economy, 2022)
Chapters 1 and 2 of this book are available for free in PDF format as Open Access from the individual product page at www.routledge.com. They have been made available under a Creative Commons Attribution-Non Commercial-No Derivatives 4.0 license.